Identifying Critical Bankability Criteria for PPP Projects: The Case of China - Lei Zhu; David Kim Huat Chua (Advances in Civil Engineering)
Public-private partnership (PPP) projects employ a high leverage in terms of debt finance needed by the private consortium. Debt finance providers need to know the bankability-related issues of PPP projects to make the timely arrangement of debt financing and avoid funding problems. However, there is still a lack of a systematic research on the bankability of PPP projects despite the worsening debt arrangement situation for PPP projects after the credit crisis and economic recession from 2008. To bridge this knowledge gap and enhance the practical debt arrangement of PPP projects, this study aims to identify and prioritize the critical bankability criteria of PPP projects. To achieve the objectives, 41 bankability-related criteria were first identified from a comprehensive literature. A structured questionnaire survey was then conducted with 31 industry experts in China who worked in financial institutes and had experienced PPP projects to investigate the relative importance of each criterion. To handle the uncertainty and vagueness of the subjective evaluation from surveys, this study analyzed the relative importance weight of each criterion using a proposed fuzzy analytical hierarchy process-based approach. The results showed that political environment, economic environment, shareholders’ credibility, financial market, legal system, public sector’s reliability, financial structure, and regulatory framework were ranked as the top eight critical bankability criteria. The findings of this study first contributed to the project finance body of knowledge for the bankability of PPP projects. Moreover, the outputs of this study would provide valuable information to the private and public sectors for formulating strategies on improving the bankability of PPP projects.